Pengaruh Pengawasan Inspektorat Kabupaten Lampung Tengah dan Partisipasi Masyarakat Terhadap Pengelolaan Dana Desa: (Studi Kasus Pada Desa Joharan Kecamatan Putra Rumbia Lampung Tengah) - Ni Made Melania E.; Syamsu Rizal (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This research aims to find out whether the Supervision of the Central Lampung Regency Inspectorate and Community Participation have an impact on village financial management in Joharan Village, Putra Rumbia District, Central Lampung. This research is a quantitative research with a random sampling approach using 94 respondents as a sample. The strategy for collecting data in this research is through a questionnaire. The population of this research is the residents of the village. This research utilizes classical assumption testing, research instrument testing, multiple linear regression testing, correlation testing, determination testing, and hypothesis testing for data analysis. The findings of this research reveal that the supervision of the Central Lampung Regency inspectorate has a positive and statistically significant impact on village fund management in Joharan village, Putra Rumbia sub-district, Central Lampung, while community participation has a positive and statistically significant impact on village fund management in Joharan Village, Putra Rumbia District, Central Lampung. In addition to the supervision factor of the Central Lampung district inspectorate and community participation, the management of village funds in the village is simultaneously positively and significantly influenced by these two variables.